2016
DOI: 10.15261/serdj.23.187
|View full text |Cite
|
Sign up to set email alerts
|

Production of Taxanes in an Ionic Liquid-medium Two Phase Culture System

Abstract: We report here the effect of a hydrophobic ionic liquid (IL), 1-hexyl-3-methylimidazolium hexafluorophosphate ([C 6 MIM][PF 6 ]), for in situ extraction of hydrophobic taxanes such as 10-deacetyl baccatin III, baccatin III, cepharomannine and paclitaxel from an aqueous medium, on the production of the taxanes by Taxus cuspidata callus in the IL-medium two phase culture system. The effect of an additional elicitor, methyl jasmonate (MJ), on the production of the taxanes was also examined. The callus growth in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Magnetic ILs such as benzyltrioctylammonium bromotrichloroferrate (III) and 1,12-di(3-hexadecylbenzimidazolium) dodecane bis[(trifluoromethyl)-sulfonyl]imide bromotrichloroferrate (III) have higher extraction efficiencies for DNA molecules [14]. We reported the enhancement of PTX and with the in situ extraction of these compounds by HMIM-PF 6 [6]. Figure 1 shows the metabolic pathway of PTX and the related taxanes from geranylgeranyl diphosphate [11].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Magnetic ILs such as benzyltrioctylammonium bromotrichloroferrate (III) and 1,12-di(3-hexadecylbenzimidazolium) dodecane bis[(trifluoromethyl)-sulfonyl]imide bromotrichloroferrate (III) have higher extraction efficiencies for DNA molecules [14]. We reported the enhancement of PTX and with the in situ extraction of these compounds by HMIM-PF 6 [6]. Figure 1 shows the metabolic pathway of PTX and the related taxanes from geranylgeranyl diphosphate [11].…”
Section: Introductionmentioning
confidence: 98%
“…Two phase culture systems using water-immiscible liquids such as organic solvents and ionic liquids (ILs) have been proposed for the in situ extraction of hydrophobic PTX from the culture medium via their hydrophobic interaction to decrease the PTX's inhibition, [3][4]. We reported on the use of more hydrophobic organic solvents such as lauryl alcohol and ILs such as 1-hexyl-3-methylimidazolium hexafluorophosphate (HMIM-PF 6 ) for the in situ extraction of paclitaxel from the aqueous medium [5][6]. As harmless solvents in contrast to conventional organic solvents, ILs have attracted attention because of their special features such as high thermal stability, negligible volatility, and selective solubility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two-phase culture system using hydrophobic solid absorbents and water-immiscible liquids has been proposed for the in situ extraction and absorption of hydrophobic paclitaxel from the culture medium, respectively [4][5][6]. We reported the effectiveness of hydrophobic organic solvents such as lauryl alcohol for the production of paclitaxel in the plant cell culture [7,8]. Recently, ionic liquids (ILs) have been paid attention to as substitutes of conventional organic solvents for the extraction of bioactive compounds from biomass.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the enhancement of paclitaxel in the plant cell culture with the in situ extraction of the compounds of the taxanes by hydrophobic ILs and 1-butyl-1-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide (P14-TFSI), which has more hydrophobic than 1-hexyl-3-methylimidazolium hexafluorophosphate (HMIM-PF 6 ) [19], enhanced the productivity of paclitaxel, BIII, 10-DAB, and cepharomannine (CM). Moreover, methyl jasmonate (MJ), a well-known elicitor which can stimulate stress responses in plants leading to enhancement of synthesis of secondary metabolites such as paclitaxel, has been used to increase the productivity of paclitaxel [8,20].…”
Section: Introductionmentioning
confidence: 99%